2014
DOI: 10.1016/j.aprim.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Patrón socioeconómico en la alimentación no saludable en niños y adolescentes en España

Abstract: Unhealthy food related with obesity show a clear socioeconomic pattern in Spanish children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
3
17
0
7
Order By: Relevance
“…[29][30][31][32][33][34][35] In addition, skipping breakfast has been associated with poor nutritional status, increased body adiposity and risk of chronic diseases. 2,36,37 The results are in agreement with earlier researchers [38][39][40] who reported that adolescents from affluent families had better quality breakfast than those belonging to the lower socioeconomic group and that skipping breakfast unhealthy dietary practices were more prevalent among adolescent girls.…”
Section: Discussionsupporting
confidence: 84%
“…[29][30][31][32][33][34][35] In addition, skipping breakfast has been associated with poor nutritional status, increased body adiposity and risk of chronic diseases. 2,36,37 The results are in agreement with earlier researchers [38][39][40] who reported that adolescents from affluent families had better quality breakfast than those belonging to the lower socioeconomic group and that skipping breakfast unhealthy dietary practices were more prevalent among adolescent girls.…”
Section: Discussionsupporting
confidence: 84%
“…Usually, childhood is the key step for adopting and consolidating eating habits. This group has been one of the groups most widely influenced by food globalization [ 18 ] given the transformation of the current food model with a wider range of industrial food, salty snacks, more soft drinks, skipping breakfast, not eating plenty of fruit, vegetables, grains and drinking milk, and abandoning traditional cuisine [ 14 , 18 , 24 ]. Thus their nutritionally inadequate diet makes them more vulnerable [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with several other studies that have reported an inverse relationship between SES and overweight, whereby the lower the SES, the higher the prevalence of overweight [ 6 , 8 , 11 , 41 , 42 , 43 ]. One explanation for this finding may be the influence SES exerts on the purchase and/or consumption of certain food products [ 12 , 13 , 44 ], for example, the high price of healthy products [ 43 , 45 ], the availability of grocery stores in certain neighborhoods offering a variety of products [ 43 ], or the possibility of eating homemade food [ 46 ]. However, other indicators such as parental educational level can also influence weight status by facilitating or restricting recommended information on this subject [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%